RESEARCH OF THE EFFICIENCY OF THE APPLICATION OF VISUAL MARKERS IN THE PROBLEMS OF LOCALIZATION INSIDE THE PREMISES - OSTAPETS, YAROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The paper investigates the effectiveness of using visual labels, such as ArUco markers, ARToolKitPlus and QR codes, for the localization of autonomous robots moving cargo in warehouses. A simulation model was developed in the Matlab environment, based on the simulation results, an estimate of losses in the conditions of label recognition errors was obtained. The results of the work can be used in the creation and analysis of the effectiveness of localization algorithms based on visual labels inside the premises.
Keywords: unmanned vehicle, localization, fiducial markers, ArUco, ARToolKitPlus, QR code, Jevois camera, simulation model